Functional Consequences of Memory Inflation after Solid Organ Transplantation - Higdon, Lauren E; Schaffert, Steven; Cohen, Rachel H; Montez-Rath, Maria E; Lucia, Marc; Saligrama, Naresha; Margulies, Kenneth B; Martinez, Olivia M; Tan, Jane C; Davis, Mark M; Khatri, Purvesh; Maltzman, Jonathan S (The Journal of immunology (1950), 2021)
CMV is a major infectious complication following solid organ transplantation. Reactivation of CMV leads to memory inflation, a process in which CD8 T cells expand over time. Memory inflation is associated with specific changes in T cell function, including increased oligoclonality, decreased cytokine production, and terminal differentiation. To address whether memory inflation during the first year after transplantation in human subjects alters T cell differentiation and function, we employed single-cell–matched TCRαβ and targeted gene expression sequencing. Expanded T cell clones exhibited a terminally differentiated, immunosenescent, and polyfunctional phenotype whereas rare clones were less differentiated. Clonal expansion occurring between pre- and 3 mo posttransplant was accompanied by enhancement of polyfunctionality. In contrast, polyfunctionality and differentiation state were largely maintained between 3 and 12 mo posttransplant. Highly expanded clones had a higher degree of polyfunctionality than rare clones. Thus, CMV-responsive CD8 T cells differentiated during the pre- to posttransplant period then maintained their differentiation state and functional capacity despite posttransplant clonal expansion.